Penerapan Media Permainan Kartu Bergambar Dengan Model Make a Match Untuk Meningkatkan Motivasi dan Hasil Belajar IPS Siswa Kelas IV SD Negeri Ujung Tanah 1 Kota Makassar - Jannah, Lu’Lul; Arifin, Jamalludin; Hakim, Ulfayani (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The purpose of this study is to enhance the learning motivation and academic performance of fourth-grade students at SD Negeri Ujung Tanah 1 in Makassar through the implementation of picture card games using the Make a Match model. The study employs a qualitative descriptive method, with data collected through interviews, observations, and documentation. Data analysis involves processes of data reduction, data presentation, and conclusion drawing. The results indicate that the application of picture card games with the Make a Match model significantly improves students' motivation and learning outcomes in Social Studies. Regarding motivation, the persistence in completing tasks increased from 50% in the first session to 90% in the third session. Students' interest in learning Social Studies rose from 47% to 95%, and enjoyment of the subject grew from 60% to 97%. Cooperation skills improved from 50% to 96%, and overall motivation shifted from 51% (low motivation) in the first session to 94% (very motivated) in the third session. In terms of learning outcomes, the pre-implementation mastery rate of 32% improved to 100% after applying the Make a Match model with picture card games. These findings demonstrate the effectiveness of this approach in fostering both motivation and academic success in Social Studies learning.